Catalytic, Kinetic, and Mechanistic Insights into the Fixation of CO2 with Epoxides Catalyzed by Phenol‐Functionalized Phosphonium Salts. Issue 1 (13th November 2020) - Hu, Yuya; Wei, Zhihong; Frey, Anna; Kubis, Christoph; Ren, Chang‐Yue; Spannenberg, Anke; Jiao, Haijun; Werner, Thomas
Abstract: A series of hydroxy‐functionalized phosphonium salts were studied as bifunctional catalysts for the conversion of CO2 with epoxides under mild and solvent‐free conditions. The reaction in the presence of a phenol‐based phosphonium iodide proceeded via a first order rection kinetic with respect to the substrate. Notably, in contrast to the aliphatic analogue, the phenol‐based catalyst showed no product inhibition. The temperature dependence of the reaction rate was investigated, and the activation energy for the model reaction was determined from an Arrhenius‐plot ( E a =39.6 kJ mol −1 ). The substrate scope was also evaluated. Under the optimized reaction conditions, 20 terminal epoxides were converted at room temperature to the corresponding cyclic carbonates, which were isolated in yields up to 99 %. The reaction is easily scalable and was performed on a scale up to 50 g substrate. Moreover, this method was applied in the synthesis of the antitussive agent dropropizine starting from epichlorohydrin and phenylpiperazine. Furthermore, DFT calculations were performed to rationalize the mechanism and the high efficiency of the phenol‐based phosphonium iodide catalyst. The calculation confirmed the activation of the epoxide via hydrogen bonding for the iodide salt, which facilitates the ring‐opening step. Notably, the effective Gibbs energy barrier regarding this step is 97 kJ mol −1 for the bromide and 72 kJ mol −1 for the iodide salt, which explains the difference in activity. Abstract : CO2 fixation : Phenol‐functionalized phosphonium salts are efficient catalysts for the synthesis of cyclic carbonates under mild and solvent‐free conditions. Their superior activity is elucidated by kinetic investigations and DFT calculations.